An improved charge pump with suppressed charge sharing effect - Na Bai (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A differential charge pump with reduced charge sharing effect is presented. The current-steering topology is adopted for fast switching. A replica charge pump is added to provide a current path for the complementary branch of the master charge pump in the current switching. Through the replica charge pump, the voltage at the complementary node of the master charge pump keeps stable during switching, and the dynamic charge sharing effect is avoided. Apply the charge pump to a 4.8 GHz band integer-N PLL, the measured reference spur is -49.7dBc with a 4-MHz reference frequency. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.2983